Tidally driven outwelling of dissolved carbon and nitrate from the largest mangroves of China - Xu, Yifei; Zhang, Zhaohui (Frontiers in Marine Science, 2025)
The Zhanjiang Mangrove National Nature Reserve (ZMNNR) is the largest mangrove in China. However, fluxes of lateral exports of dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and nitrate from the ZMNNR remain unknown, hindering us from evaluating its blue carbon capacity and its resilience to environmental changes. We conducted a comprehensive study of temporal variations in DIC, DOC, nitrate, and sulfate in creek and pore waters, and time-series measurements of 222Rn in creek waters, in response to tidal cycles. Nitrate and sulfate concentrations varied in tidal cycles, forming a tightly negative correlation. DIC and DOC were significantly rich in, but nitrate was substantially depleted in pore waters compared to creek waters. Depleted δ13C values of DIC and DOC in tidal creek waters suggest that both of them were predominantly from organic matter derived from mangroves. Radiocarbon ages of DIC ranged from 149 to 236 years, suggesting minimal or absent mineralization of aged (i.e., centuries-old) organic matter. Time-series measurements of 222Rn in creek waters revealed pore water exchange rate at 14.2 ± 24.5 cm d−1, and the lateral fluxes of DIC and DOC from the mangroves to the neighboring Yingluo Bay, based on an FVCOM model, were 411.6 ± 311.8 and 104.5 ± 145.7 mmol m−2 d−1, respectively. Outwelling fluxes of dissolved carbon were estimated to be equivalent to 7.7% ± 6.8% of annual carbon fixed by mangroves in the study area. The flux of nitrate from the study area to Yingluo Bay was 8.5 ± 7.6 mmol m−2 d−1, making mangroves the sink of nitrate and the source of ammonium.